2021
DOI: 10.1371/journal.pone.0256735
|View full text |Cite
|
Sign up to set email alerts
|

Understanding molt control switches: Transcriptomic and expression analysis of the genes involved in ecdysteroidogenesis and cholesterol uptake pathways in the Y-organ of the blue crab, Callinectes sapidus

Abstract: The crustacean molting process is regulated by an interplay of hormones produced by the eyestalk ganglia and Y-organs (YO). Molt-inhibiting hormone and crustacean hyperglycemic hormone released by the sinus gland of the eyestalk ganglia (EG) inhibit the synthesis and secretion of ecdysteroid by the YO, hence regulating hemolymph levels during the molt cycle. The purpose of this study is to investigate the ecdysteroidogenesis pathway, specifically genes linked to changes in ecdysteroid levels occurring at early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 78 publications
1
10
0
1
Order By: Relevance
“…Clustering with CD-HIT-EST increases single-copy and reduces duplicate BUSCOs, supporting a clustering strategy. These results and tendencies are comparable to BUSCO outputs generated for other decapod crustaceans [ 20 , 42 , 43 ]. Interestingly, the N50 length of this assembly is similar to those observed for S. paramamosain [ 44 ] and Metapenaeus bennettae [ 45 ].…”
Section: Discussionsupporting
confidence: 79%
“…Clustering with CD-HIT-EST increases single-copy and reduces duplicate BUSCOs, supporting a clustering strategy. These results and tendencies are comparable to BUSCO outputs generated for other decapod crustaceans [ 20 , 42 , 43 ]. Interestingly, the N50 length of this assembly is similar to those observed for S. paramamosain [ 44 ] and Metapenaeus bennettae [ 45 ].…”
Section: Discussionsupporting
confidence: 79%
“…Five of the transcripts have a close match for CYP49a1, indicating this enzyme plays a key role in P. ornatus. CYP49a1 is said to be an ecdysone responsive gene, with expression in the Y-organ and ovary, and to a lesser extent, the heart [62]. It has previously been suggested that its expression is likely dependent on the developmental stage in arthropods, with upregulation in early premoult animals, with expression similar to Spook and neverland in the blue crab, Callinectes sapidus [62].…”
Section: Discussionmentioning
confidence: 99%
“…CYP49a1 is said to be an ecdysone responsive gene, with expression in the Y-organ and ovary, and to a lesser extent, the heart [62]. It has previously been suggested that its expression is likely dependent on the developmental stage in arthropods, with upregulation in early premoult animals, with expression similar to Spook and neverland in the blue crab, Callinectes sapidus [62]. In the adult tissues, only three of the uncharacterised CYP450s showed differential expression, all three putative CYP49a1.…”
Section: Discussionmentioning
confidence: 99%
“…E2 synthesis in crustaceans is the same as described in vertebrates, wherein StAR is required for cholesterol movement. This step is also known to critical for ecdysteroidogenesis in the Y-organ ( 63 ).…”
Section: Discussionmentioning
confidence: 99%